THE THEME OF AI TECHNOLOGIES IN AMERICAN SCIENCE FICTION - Akhmedov Rafael Sharifovich (TADQIQOTLAR.UZ, 2024)
Abstract. Artificial Intelligence (AI) has long captivated the imagination of American science fiction writers and filmmakers, serving as a central theme in exploring the possibilities and consequences of advanced technology. From the early days of American science fiction literature, AI has been portrayed in various forms, often as a reflection of society's fears and aspirations regarding technology. As the genre evolved over time, AI characters in contemporary American science fiction films have become more complex and nuanced, reflecting the changing attitudes towards technology and its integration into everyday life. However, along with the advancements in AI technology depicted in these narratives come ethical implications that are increasingly relevant to our own society. This research paper delves into the representation of AI in early American science fiction literature, the evolution of AI characters in contemporary American science fiction films, and the ethical dilemmas surrounding AI technology in American science fiction narratives. By analyzing these aspects, this paper aims to shed light on the ways in which AI is depicted in American science fiction and the broader implications it holds for society.